Forest Trees and their Improvement - Shetty, K. A. Bhoja (Indian Forester, 1957)
The application of genetics, cytology and other allied sciences has not been given any serious consideration in Indian forestry hitherto. Mass selection which has been the rule in all our afforestation and plantation programmes has to give place to the exploration of individual variants and selective hybridization in order to ensure the propagation of only the most superior genotypes. The role of forest tree breeding in the control of pests and diseases has been stressed. The lines on which the geneticist can contribute towards progress in Indian forestry have been briefly outlined.